2016
DOI: 10.1016/j.bjan.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da insuflação de dióxido de carbono sobre a oxigenação cerebral regional durante cirurgia laparoscópica em crianças: um estudo prospectivo

Abstract: Carbon dioxide insufflation during pneumoperitoneum in pediatric patients may not affect cerebral oxygenation under laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Westgarth-Taylor et al ( 21 ) found an increase in cerebral oxygenation after insufflation in paediatric patients who had undergone laparoscopic surgery. In the other two studies, they found no change in cerebral oxygenation due to pneumoperitoneum compared to the open technique ( 22 , 23 ). Tsypin et al ( 24 ) reported an average reduction of 3% in regional cerebral tissue saturation in children during gynaecological laparoscopic interventions.…”
Section: Discussionmentioning
confidence: 88%
“…Westgarth-Taylor et al ( 21 ) found an increase in cerebral oxygenation after insufflation in paediatric patients who had undergone laparoscopic surgery. In the other two studies, they found no change in cerebral oxygenation due to pneumoperitoneum compared to the open technique ( 22 , 23 ). Tsypin et al ( 24 ) reported an average reduction of 3% in regional cerebral tissue saturation in children during gynaecological laparoscopic interventions.…”
Section: Discussionmentioning
confidence: 88%
“…Subtotal gastrectomy is a major operation for gastric cancer, the operative time is long and is further extended by waiting for pathological results and dissecting local lymph nodes. When the long operative time under general anesthesia causes hypoventilation or other respiratory system complications, the gas exchange capacity is impaired and desaturation rSO 2 often results, which may be significantly correlated with neurological complications, cognitive function, and prolonged length of stay (6,7). Therefore, it is important to detect early diagnosis indicators and serological markers of POCD so that it can be prevented after subtotal gastrectomy.…”
Section: Introductionmentioning
confidence: 99%